2004
DOI: 10.1021/bi036175d
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Mechanism of Bioluminescence Color Determination in Firefly Luciferase

Abstract: Beetle luciferases (including those of the firefly) use the same luciferin substrate to naturally display light ranging in color from green (lambda(max) approximately 530 nm) to red (lambda(max) approximately 635 nm). In a recent communication, we reported (Branchini, B. R., Murtiashaw, M. H., Magyar, R. A., Portier, N. C., Ruggiero, M. C., and Stroh, J. G. (2002) J. Am. Chem. Soc. 124, 2112-2113) that the synthetic adenylate of firefly luciferin analogue D-5,5-dimethylluciferin was transformed into the emitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
190
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(201 citation statements)
references
References 43 publications
(86 reference statements)
10
190
0
1
Order By: Relevance
“…Recently, however, Branchini and coworkers suggested that luciferase modulates emission color by controlling the resonancebased charge delocalization of the anionic keto form of excited oxyluciferin (28). Theoretical studies indicated that the degree of polarization of oxyluciferin phenolate/ keto-enolate groups, under influence of the active site residues, could be determinant of bioluminescence colors (27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, Branchini and coworkers suggested that luciferase modulates emission color by controlling the resonancebased charge delocalization of the anionic keto form of excited oxyluciferin (28). Theoretical studies indicated that the degree of polarization of oxyluciferin phenolate/ keto-enolate groups, under influence of the active site residues, could be determinant of bioluminescence colors (27).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the benzothiazolyl moietyis tightly buried and stabilized in the binding site, through hydrophobic forces and phenolate interaction with R215, it is possible that at least during the emitting step, the thiazolinic moiety could be exposed to a more polar environment in the case of PxRE luciferase and to a more hydrophobic environment in the case of PxGR luciferase. According to the recently proposed theory of polarization of phenolate and keto/enolate groups (27,28), the substitution of R215 would be expected to affect the emission spectrum by increasing the polarization of excited oxyluciferin, if the keto/enolate moiety is not polarized. This is supported by the experimental observation that the substitution of R215 affects the bioluminescence spectrum only in the green emitting railroadworm and firefly luciferases, but not in the red emitting PxRE luciferase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between l = 600-800 nm, the absorption of light by Hb decreases by a factor of approximately 50, resulting in less attenuation of red light. This wavelength range is within what is termed the "bio-optical window" and there has been much focus on engineering red-shifted Fluc enzymes that have maximum emission wavelengths in this range, [10][11][12][13][14][15] but these have peaked at wavelengths less than l = 645 nm.The most red-shifted luciferin analogues to date [16] are based upon amino derivatives (Figure 1 b), for example cyclic aminoluciferin (3 a: l max = 599 nm; 3 b: l max = 607 nm), [17] seleno-d-aminoluciferin (4: l max = 600 nm), [18] and a rationally designed 4-(dimethylamino)phenyl derivative conjugated to a thiazoline group (5: l max = 675 nm). [19] In particular cyclic aminoluciferin derivative 3 a has been shown to give improved bioluminescence imaging compared to luciferin (LH 2 ; 1) at dilute concentrations where the intracellular concentration of the luciferin or analogue is limiting.…”
mentioning
confidence: 99%
“…Between l = 600-800 nm, the absorption of light by Hb decreases by a factor of approximately 50, resulting in less attenuation of red light. This wavelength range is within what is termed the "bio-optical window" and there has been much focus on engineering red-shifted Fluc enzymes that have maximum emission wavelengths in this range, [10][11][12][13][14][15] but these have peaked at wavelengths less than l = 645 nm.…”
mentioning
confidence: 99%